Study of a Two-Step Centrifugation Protocol for Concentrating Cells and Growth Factors in Bovine Platelet-Rich Plasma - Claudia M. Gutiérrez; Catalina López; Carlos E. Giraldo; Jorge U. Carmona (Veterinary Medicine International)
There is a lack of information about the methods used for bovine platelet-rich plasma (PRP)/platelet-rich gel (PRG) procurement, including information on platelet (PLT), white blood cell (WBC) in PRP, and growth factor release from PRG supernatants. The aims of this study were to compare and to correlate the PLT, WBC, transforming growth factor beta-1 (TGF-β1), and platelet-derived growth factor BB (PDGF-BB) concentrations in bovine whole blood, plasma, and four PRP layers and their respective PRG supernatants: A and B (obtained by a single centrifugation tube method at 720g/5 min) and C and D (obtained by a double centrifugation tube method, by using two centrifugation episodes at 720g/5 min). PLT and WBC counts were significantly higher in PRP-C, followed by whole blood, PRP-A, PRP-B, and PRP-D. TGF-β1 concentrations were significantly higher in PRG-B supernatants and its correspondent PRP-B lysate when compared to the other PRG supernatants and plasma. Supernatants from PRG-A, PRG-B, and PRG-D had equivalent TGF-β1 concentrations. PDGF-BB concentrations were not statistically different between the hemoderivatives. Significant Pearson correlations were noted between PLT counts and WBC counts (0.8) and between PLT counts and PLT distribution width (0.6). Further studies should be performed to assess the potential clinical applications of these PRPs.